EVALUATION OF USABILITY AND USER INTERFACE DESIGN TO ENHANCE USER EXPERIENCE THROUGH HEURISTIC EVALUATION APPROACH AND LEAN UX METHOD WITH ISO 13407 STANDARDS Case Study : SISTER Kemendikbud Ristek RI - Gigih Forda Nama; Siti Waqiah; Mahendra Pratama (Jurnal Rekayasa Lampung, 2026)
Abstract: Sistem Informasi Sumberdaya Terintegrasi (SISTER) is a system that integrates services within the scope of higher education resources and data integration with the Higher Education Database (PDDIKTI). This study aims to evaluate usability using the Heuristic Evaluation questionnaire, Usability Testing in the Lean UX phase, and ISO 13407 Evaluation in the final testing phase. The distribution of the questionnaire resulted in 676 responses, with 397 samples used and involving 3 evaluators in Usability Testing during the Lean UX phase. In the final phase, the evaluation was conducted according to ISO 13407 standards, involving 9 respondents to test the prototype using task scenarios. The evaluation results showed an average score of <1200 and a mean score of <3, indicating a low level of user satisfaction with the system. Additionally, a TCR value of <65% also indicated that the system's interface was considered fair or average by users. On the other hand, the Usability Testing results identified improvements related to redundant pop-up messages and over-engineering of outline buttons in the prototype. This list of issues served as a reference for compiling recommendations and design improvements based on the 10 usability heuristics. After making improvements, the ISO 13407 evaluation results achieved a score of 80.89%, indicating a Good qualification.